DESIGN OF PROTOTYPE DYNAMIC AC POWER MACHINE WITH EQUIVALENT CIRCUIT MODELING (TORQUE SPEED CURVE OF INDUCTION MOTOR 1,1, KW) - Abidin, Zainal; Adam, Adam (Universitas Nusa Cendana, 2017)
Squirrel cage induction motors are widely used in electric motor drives due to their satisfactory mechanical characteristics (torque, current, overloading) and small dimensions, as well as their low price. When starting an induction motor, a large current is required for magnetizing its core, which results in a low power factor, rotor power losses and a temperature rise in the windings. None of these parameters should reach values beyond certain limits until the motor reaches nominal speed.The speed of an induction motor 1,1kW is affected very little by fluctuations of voltage. The greater the supply voltage of the motor, the induction motors speed will increase. The torque values (Tstart, TSmax and Tmax) are affected by the value of the motor supply voltage: (Vp-nl :Â 132.8, Tstart1 : 7.4, T S-max1 : 0.4, Tmax1 : 9.9) V, (Vp-nl :Â 127.0, Tstart2 : 4.8, T S-max1 : 0.3, Tmax1 : 8.4) V and (Vp-nl :Â 121.3, Tstart3 : 3.3, T S-max3 : 0.2, Tmax3 : 7.1) V. Stator current (IL-nl ; 2.5, 2.2, 1.9 ) Amp rises gradually on account of the increase in magnetising current (Im : 2.5, 2.2, 1.9) Amp. The magnetising current required to produce the stator flux. The component of the stator current which provides the ampere-turns balancing the rotor ampere-turns will steadily diminish as the rotor current (IL-nl) decrease with the increase in rotor speed (nr).